3rd request of extending suspension period arising from Covid-19 for BRACU project - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the 3rd request of extending suspension period arising from Covid-19 for BRACU new campus project.